Psoriasis, bone and bowel: a comprehensive review and new insights - Fakhreddin Sabooniha (Exploration of Musculoskeletal Diseases)
Psoriasis is a chronic immune-mediated disorder affecting about 2% of the population worldwide which is associated with significant morbidity. The disease usually presents as raised, well-demarcated erythematous plaques with adherent silvery scales. Psoriasis can appear at any age but it has two peaks occurring at 15–20 and 55–60 years of age. It affects males and females equally. Despite the multitude of investigations about psoriasis and even development of drugs with satisfactory results, its pathogenesis is not fully understood yet and its course is unpredictable. Various environmental triggers, e.g., obesity, stress and drugs may induce disease in genetically susceptible patients. Although psoriasis was considered primarily as a disease of the skin, more investigations have been revealed its systemic nature. Psoriatic arthritis (PsA) may complicate up to one-third of cases of psoriasis vulgaris (PV). Also, the association between psoriasis and a variety of other immune-mediated disorders such as inflammatory bowel disease (IBD) and celiac disease (CD) has been confirmed in various studies. Moreover, a growing body of evidences indicates that psoriasis shares some common histological and phenotypical properties with the spectrum of osteoimmunological diseases such as Paget’s disease of bone (PDB). Thus, exploring the common molecular and genetic mechanisms underlying psoriasis and related disorders is of paramount importance for better elucidating disease pathogenesis and designing more targeted treatments.